Moments before the flood - De Keyzer, Carl, 1958- (Houten : Lannoo ; Woodbridge : ACC Distribution [distributor], 2012)
For four years, Carl De Keyzer travelled four months a year along the coasts of Europe, from the far north to the deep south. He photographed alienating landscapes, desolate beaches, deserted hotels, piers and dramatic and terrifying clouds: beautiful but ominous images with a high David Lynch twist. "Moments before the Flood" is a photography of waiting. Carl De Keyzer portrays the uncanny of the vague and uncertain, with a masterful eye for beauty and an unparalleled sense of irony.
Keywords: Keyzer, Carl de, -- 1958-.; Coasts -- Europe -- Pictorial works; Flood control -- Europe -- Pictorial works; Photography, Artistic; Sea level -- Europe -- Pictorial works